OPTIMASI DOSIS EKSTRAK ETANOL BUAH DUKU (Lansium Domestikum Corr.) UNTUK EFEKTIVITAS DIURETIK TERHADAP TIKUS JANTAN GALUR WISTAR - Niza, Hairun; Fahrozi, Hikmal (Jurnal Farmasi (Journal of Pharmacy), 2024)
Research has been carried out on optimizing the dose of ethanol extract of Duku fruit (Lansium domesticum corr) for the effectiveness of diuretics in male Wistar rats. This research uses quantitative methods. The animals used in this research were 25 male Wistar rats and were divided into 5 groups that had passed the acclimation period and had passed the urine volume collection period. Each group was given a different preparation, group I negative control was Na-CMC 0.5%, group II positive control furosemide 36 mg/kgBB, group III ethanol extract of duku fruit 50 mg/kgBB, group IV ethanol extract of duku fruit 100 mg /kgBW, and group V extra ethanol duku fruit 150 mg/kgBB. Urine volume measurements were carried out on days 8 to 21 every 12 hours. The data obtained were analyzed using statistical tests, Levene's test, Shapiro Wilk, two-way anova, and post hoc tests. The results of this study show that a dose of 150 mg/kgBB has diuretic activity in duku fruit plants with the average volume of urine collected in the 2nd week being 7.46 ± 3.27, in the 3rd week the average volume urine 9.92 ± 3.11. In the positive control, furosemide as a comparison, the average urine volume was 6.21 ± 3.56 in the 2nd week and in the 3rd week, the average urine volume was 8 ± 3.60.